Bsre ʼphoʼi ʼkhrul ʼkhor spyiʼi sṅon rjes kyi pa rnams kyi zin bris brjed byaṅ blo dman dgaʼ ʼbskyed ces bya ba bźugs so - Nāḍapāda (s.n., 1976)
Preliminary instructional notes on the esoteric yogic practice of the Six Doctrines of Nāropa according to the Drukpa Kargyudpa tradition.